AKURASI SINYAL TRANSISI DALAM TULISAN ARGUMENTATIF: STUDI KUALITATIF DESKRIPTIF - Lisbeth Sirait; Chatrine Meylani Chen (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2026)
This research examines the categories and precision of transitional devices utilized by first-semester English Literature students at Universitas Kristen Indonesia in their argumentative compositions. Informed by the theoretical perspectives of Oshima and Hogue (2006), Halliday and Hasan (1976), and Hyland (2007), the study employs a descriptive qualitative methodology to scrutinize 28 students’ essays. The results indicate a primary dependence on additive and contrastive transitions, coupled with infrequent application of causal and temporal connectors. Although students exhibit a rudimentary grasp of fundamental linkers such as “and,” “also,” and “however,” their vocabulary diversity and grammatical accuracy are notably restricted. Instances of inaccuracy encompass superfluous repetition, colloquial expressions, and sparse incorporation of sophisticated transitional phrases. ("Additive transitions accounted for 75 tokens of all markers used, while temporal transitions were the least frequent at 4 tokens.") These tendencies mirror developmental phases in second language acquisition and highlight the necessity for genre-specific instructional strategies. The research informs curriculum enhancement in accordance with the Common European Framework of Reference (CEFR) and outcome-based education (OBE) principles, stressing the significance of cohesive elements in cultivating academic writing competence.